2022
DOI: 10.3390/brainsci12010097
|View full text |Cite
|
Sign up to set email alerts
|

The Semantics of Natural Objects and Tools in the Brain: A Combined Behavioral and MEG Study

Abstract: Current literature supports the notion that the recognition of objects, when visually presented, is sub-served by neural structures different from those responsible for the semantic processing of their nouns. However, embodiment foresees that processing observed objects and their verbal labels should share similar neural mechanisms. In a combined behavioral and MEG study, we compared the modulation of motor responses and cortical rhythms during the processing of graspable natural objects and tools, either verb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…The embodied perspective on language is now supported by several studies showing that activation of neural substrates processing the sensory and motor aspects of the world is not only associated with the processing of language referring to concrete aspects of the world (Buccino et al, 2005;Tettamanti et al, 2005;Gough et al, 2012Gough et al, , 2013Marino et al, 2013Marino et al, , 2014Visani et al, 2022) but is also causal to the understanding of concrete language (e.g., Bak et al, 2006;Sato et al, 2008;Kemmerer et al, 2012;Tremblay et al, 2012;Cardona et al, 2013;Fernandino et al, 2013;Desai et al, 2015;Klepp et al, 2015;Buccino et al, 2018; for review Buccino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The embodied perspective on language is now supported by several studies showing that activation of neural substrates processing the sensory and motor aspects of the world is not only associated with the processing of language referring to concrete aspects of the world (Buccino et al, 2005;Tettamanti et al, 2005;Gough et al, 2012Gough et al, , 2013Marino et al, 2013Marino et al, , 2014Visani et al, 2022) but is also causal to the understanding of concrete language (e.g., Bak et al, 2006;Sato et al, 2008;Kemmerer et al, 2012;Tremblay et al, 2012;Cardona et al, 2013;Fernandino et al, 2013;Desai et al, 2015;Klepp et al, 2015;Buccino et al, 2018; for review Buccino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore defined the regions of interest (ROIs) for this study as the anterior (AIP) and posterior (CIP) areas of the LIPS and the anterior (SMG) and posterior (AG) areas of the LIPL. Viewing hand-manipulable objects activates the precentral cortex 27 , 48 , 49 ; such activity might be altered by hand constraint. Therefore, it would be beneficial to simultaneously record the LIPL and premotor cortex.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the neural structures implicated in the execution and understanding of observed actions also appear involved in the understanding and processing of action-related language (Vigliocco et al, 2011 ; Marino et al, 2014 ; Borghi and Riggio, 2015 ; Buccino et al, 2016 , 2018 ; García and Ibáñez, 2016 ; Sakreida et al, 2016 ; Zhang et al, 2016 ; Horoufchin et al, 2018 ; Garofalo et al, 2022 ; Visani et al, 2022 ). In this respect, accumulating empirical evidence suggested that the sensorimotor and even emotional systems involved in experiencing the content expressed by verbal material are causally involved in understanding the content of that linguistic stuff (Pulvermüller, 2002 , 2010 ; Barsalou, 2008 ; Fischer and Zwaan, 2008 ; Gallese, 2008 ; Jirak et al, 2010 ; Buccino et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this interpretation, Transcranial Magnetic Stimulation (TMS) studies showed a decrease in Motor-Evoked Potentials (MEPs) during verb listening (Buccino et al, 2005 ). Furthermore, a weaker suppression of Beta band oscillations was found when motor responses are given with the same body part normally used to perform the action expressed by the verb (Klepp et al, 2015 ; Visani et al, 2022 ). Beta band oscillations are the main rhythm deriving from the motor cortex, and it is characterized by a pattern of suppression and rebound during movement (Pfurtscheller and Lopes da Silva, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation